Opening the black box of integration moving toward a standardized integration architecture. - Lehmann, Mike
If you've been working with integration technologies for any length of time, you're well aware of the freight train of standards that has been careening through the industry during the last five years. These standards, particularly in the Web services space, are on the verge of doing to proprietary integration servers what SQL and J2EE standards did to database and middle-tier servers of days gone by.